Problematika nakládání s dešťovými vodami z komunikací - Oprchalová, Marie (Vysoké učení technické v Brně. Fakulta stavební)
Zvyšováním intenzity dopravy na stávajících komunikacích, výstavba nových dálnic a rychlostních komunikací způsobuje větší znečištění povrchových vod látkami, které pocházejí z údržby cest a provozu vozidel. Proto jsou zařízení na úpravu těchto kontaminovaných vod jako např. odlučovače lehkých kapalin v dnešní době velmi aktuální. Předmětem této práce bylo testování možnosti zvýšení účinnosti mechanického odlučovače lehkých kapalin instalací různých typů vestaveb. Cílem bylo zjistit účinnost této konvenční technologie, která je energeticky a technicky nenáročná a její využitelnost pro předčištění (předúpravu) před případným dalším stupněm čištění.

Transportation has unfavorably influence on a quality of enviroment. Increase of traffic leads to construction of new motorways and to intensify the traffic on current comunications. A consequence is more polluted hard surfaces, when surface-wash contaminate soil, surface water and underground water. Devices for treating contamined water, such as oil-separators, are very actual in these days. The subject of this thesis was to test the possibilities of increasing effectiveness of mechanical separator for light liquids by installing various types of constructions. Target was to determine effectiveness of this conventional technology, which is energetically and technically simple and find out applicability for first step cleaning and further usage.
Problems of disposal with rainwater from a communication
Keywords: Odlučovač lehkých kapalin; dešťové vody; zaolejované vody; separace ropných látek; Separator systems for light liquids; rainwater; oily water; separator of oil substances